Elaboración del manual de operaciones, para el área de coctelería del laboratorio de servicios de la carrera de ingeniería en ecoturismo de la Universidad Técnica de Cotopaxi - Acosta Clavijo, Ángel Danilo (2013)
The research was used to implement the preparation and presentation of beverages, to be held in the cocktail area Services Laboratory at Technical University of Cotopaxi. The document is prepared according to standards ISO 9000 and 9001 Quality Management System. The services laboratory intended to be a reinforcement in the theoretical and the development of student' technical and practical skills through joint support of the teacher and student. This guide is developed based on literature reviews of cocktails, aimed at the manufacture of beverages subject to quality standards, direct diagnosis in the cocktail area, establishing the different processes in the development of pampering to be made by students Ecotourism career….